Effect of Saxagliptin on Circulating Endothelial Progenitor Cells and Endothelial Function in Newly Diagnosed Type 2 Diabetic Patients - Li, Fang; Chen, Jiachao; Leng, Fei; Lu, Zhiqiang; Ling, Yan (Experimental and Clinical Endocrinology & Diabetes, 2017)
Endothelial dysfunction is associated with the risk of cardiovascular complications in diabetic patients. Endothelial progenitor cells (EPCs) and flow-mediated dilation (FMD) are common markers of endothelial function. In this study, we aim to investigate whether the DPP-4 inhibitor saxagliptin modulate EPCs number and FMD in newly diagnosed, treatment-naive type 2 diabetic patients. This was a controlled, randomized, open-label clinical trial. Saxagliptin group and metformin group consumed either saxagliptin 5 mg per day or metformin 1 500 mg per day respectively for 12 weeks. Changes of FMD and EPCs number after 12-week intervention were the primary endpoints. 31 patients were initially enrolled and randomized to saxagliptin group (n=16) and metformin group (n=15). 27 patients completed the trial (saxagliptin group n=14 and metformin group n=13), and 4 patients dropped out during the study. FMD and EPCs number increased significantly in both saxagliptin group and metformin group, and there was no significant difference between groups. 2-h postprandial plasma glucose, HbA1c and diastolic blood pressure improved significantly in both groups, and there was no significant difference between groups. Saxagliptin and metformin had comparable beneficial effects on endothelial function.
Keywords: type 2 diabetes; endothelial progenitor cell; flow-mediated dilation; dipeptidyl peptidase-4 inhibitor; saxagliptin